A Cost-Effective and Rapid Manufacturing Approach for Electrochemical Transducers with Magnetic Beads for Biosensing - Milica Govedarica; Ivana Milosevic; Vesna Jankovic; Radmila Mitrovic; Ivana Kundacina; Ivan Nastasijevic; Vasa Radonic (Micromachines)
Biosensors as advanced analytical tools have found various applications in food safety, healthcare, and environmental monitoring in rapid and specific detection of target analytes in small liquid samples. Up to now, planar electrochemical electrodes have shown the highest potential for biosensor applications due to their simple and compact construction and cost-effectiveness. Although a number of commercially available electrodes, manufactured from various materials on different substrates, can be found on the market, their high costs for single use and low reproducibility persist as major drawbacks. In this study, we present an innovative, cost-effective approach for the rapid fabrication of electrodes that combines lamination of 24-karat gold leaves with low-cost polyvinyl chloride adhesive sheets followed by laser ablation. Laser ablation enables the creation of electrodes with customizable geometries and patterns with microlevel resolutions. The developed electrodes are characterized by cyclic voltammetry and electrochemical impedance spectroscopy, scanning electronic microscopy, and 3D profiling. To demonstrate the manufacturing and biosensing potential, different geometries and shapes of electrodes were realized as the electrochemical transducing platform and applied for the realization of magnetic bead (MB)-labeled biosensors for quantitative detection of food-borne pathogens of Salmonella typhimurium (S. typhimurium) and Listeria monocytogenes (L. monocytogenes).